The Comparison of Marital and Family Factors Between Singaporean Monocultural and Intercultural Couples - Skowroński, Dariusz P.; Tay, Daniel Justin Fong; Ho Wen Wan, Michelle; Ying Cherie, Toh Shi; Frenandez, Tricia Marjorie; Waszyńska, Katarzyna (Wydawnictwo Naukowe UAM, 2014)
The number of intercultural marriages in Singapore has recently been on the rise and research has found that these mixed marriages and relationships tend to have lower levels of marital satisfaction in comparison to monocultural marriages. To determine whether the level of marital satisfaction will be higher for monocultural couples as compared to intercultural couples, a 40-item questionnaire and an 8-item interview was developed based on 8 different factors of couple dynamics and family factors. 10 monocultural couples and 11 intercultural couples were recruited to complete the questionnaire and five monocultural couples, and five intercultural couples from this participant pool participated in an additional interview. It was hypothesized that the marital satisfaction scores, based on both couple dynamics and family factors, will be higher in monocultural couples as compared to intercultural couples. Contrary to that, results showed that intercultural couples demonstrated higher marital satisfaction scores as compared to monocultural couples. Arguably, it may be possible that Singapore and the other parts of the world might differ by having a strong foundation of interethnic ties, which may have made intercultural marriages more widely accepted.
Analiza porównawcza czynników małżeńskich i rodzinnych w związkach mono- i międzykulturowych w Singapurze
Keywords: intercultural marriages; marital factors; family factors; marital satisfaction